Cardiology : acronyms & abbreviations - Jablonski, Stanley (Hanley & Belfus, 2002)
(Hanley & Belfus) Spinoff from the Dictionary of Medical Acronyms & Abbreviations, 4th ed., c2001. Pocket-sized text focuses entirely on cardiology terminology. Softcover. DNLM: Cardiology--Abbreviations.
Keywords: kardiologie; Cardiology; lingvistika, lékařská terminologie; Abbreviations as Topic; terminologie jako téma; Terminology as Topic; zkratky jako téma